TINJAUAN YURIDIS TERHADAP PERILAKU PENGGUNA HELM DI UNIVERSITAS HALUOLEO - Widiasih, Ni Putu Sri (Lembaga Penelitian dan Pengabdian Masyarakat, 2018)
Violations committed by motorists with not using a helmet shows compliance (compliance) are low traffic rules as regulated in section 57 subsection (2) of Act No. 22 of year 2009 about traffic Transport and streets. This type of research is conducted with the normative-legal research efforts are empirical. The research results showed that the factors cause motorists not wearing a helmet at the cross roads and surrounding A H.E. Mokodompit still in Kecamatan Kambu is a factor of consciousness and behavior, because almost all violations and traffic accidents on the road sekitasrnya and H.E. à Mokodompit that Kecamatan Kambu is still in its primary cause is the rider. These factors gave rise to differences of level of knowledge and/or understanding of the people against the prevailing rules resulted in a disparity that potentially gave rise to traffic problems in particular knowledge of the importance of the benefits the use of helmets for motorbike riders of vehicles that do not wear a helmet, both between road users themselves as well as between road users with apparatus that served to carry out law enforcement on highways, environmental factors contribute active in creating behavior-behavior that deviates. The citizens of the society like the breach of rules that have been set out in the legislation are likely to form a bad or aberrant personality on the individual efforts being done Satlantas Polres Kendari in tackling traffic offences caused by motorcyclists not wearing a helmet at the cross streets of H.E. à Mokodompit is by way of enforcing methods of pre-emptif, is an effort or prevention efforts against irregularities.